2018
DOI: 10.1108/ccsm-08-2017-0095
|View full text |Cite
|
Sign up to set email alerts
|

Expatriates adjustment through transformation of social identity of Chinese expatriates working in Pakistan

Abstract: Purpose The purpose of this paper is to investigate the process of Chinese expatriates’ adjustment in Pakistan through integrating the U-curve model and social identity theory. It has also highlighted the importance of engaging in strong social ties and their contribution in expatriates’ adjustment. Design/methodology/approach Data were collected through semi-structured interviews from 30 Chinese expatriates working as directors, deputy directors, senior managers, managers and assistant managers in Chinese o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 117 publications
1
35
0
Order By: Relevance
“…Past studies have also confirmed that Chinese expatriates face different challenges related to their work in Pakistan. In addition, the main concern shown by the respondents is the delaying of tasks and working habits of Pakistani people, resulting in obstacles in their adjustment [46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Past studies have also confirmed that Chinese expatriates face different challenges related to their work in Pakistan. In addition, the main concern shown by the respondents is the delaying of tasks and working habits of Pakistani people, resulting in obstacles in their adjustment [46].…”
Section: Discussionmentioning
confidence: 99%
“…The study also highlights challenges regarding Chinese expatriate's non-works factors that affect their adjustment in Pakistan (see Table 3). The major challenges are the "language barrier" and "cultural differences" in Pakistan [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transformation in social identities of individuals as a result of working in diverse social settings has been explored in a large body of literature (Hogg et al, 2017;Nadeem & Mumtaz, 2018;Peltokorpi & Zhang, 2020). The above literature has integrated social identity theory for suggesting a critical role of membership of new social groups for individuals (Jetten et al, 2002).…”
Section: Introductionmentioning
confidence: 99%